2008
DOI: 10.1093/ajcn/87.5.1356
|View full text |Cite
|
Sign up to set email alerts
|

How pre- and postnatal risk factors modify the effect of rapid weight gain in infancy and early childhood on subsequent fat mass development: results from the Multicenter Allergy Study 90

Abstract: The occurrence of rapid weight gain between birth and 2 y and the magnitude of its effect on BF% development in AGA children is influenced by both intrauterine and postnatal exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 50 publications
9
92
0
2
Order By: Relevance
“…10,74,75 Studies have shown an association with a mother's weight gain during pregnancy and a child's increased risk of being obese later in life. [74][75][76] To determine whether a mother's weight gain during pregnancy was the cause and not the infant's surrounding environment, two studies examined the mother and father's BMI values and their relationship to the child's BMI value and found that the association between maternal BMI and child BMI was statistically similar to the paternal BMI and child BMI, suggesting that increased adiposity could be more related to the postnatal environment and not a maternal effect. 10,77 Secondhand Smoke Exposure (SHS) The role of prenatal cigarette smoke exposure and childhood obesity has long been a focus of many adverse health outcomes including obesity.…”
Section: Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…10,74,75 Studies have shown an association with a mother's weight gain during pregnancy and a child's increased risk of being obese later in life. [74][75][76] To determine whether a mother's weight gain during pregnancy was the cause and not the infant's surrounding environment, two studies examined the mother and father's BMI values and their relationship to the child's BMI value and found that the association between maternal BMI and child BMI was statistically similar to the paternal BMI and child BMI, suggesting that increased adiposity could be more related to the postnatal environment and not a maternal effect. 10,77 Secondhand Smoke Exposure (SHS) The role of prenatal cigarette smoke exposure and childhood obesity has long been a focus of many adverse health outcomes including obesity.…”
Section: Sleepmentioning
confidence: 99%
“…These studies found an association between maternal prenatal smoking and childhood obesity even after accounting for various confounding factors. 12,16,76,[78][79][80][81][82][83][84][85][86][87][88][89][90][91] Although there is a compelling link between prenatal smoking and childhood obesity, it is not always clear-cut for both genders and all maternal smoking levels. 86,87 One study followed children from 2 to 10 years of age and found that males whose mothers smoked during pregnancy had a lower BMI at age 2 years than those born to non-smoking mothers or had partners who smoked.…”
Section: Sleepmentioning
confidence: 99%
“…17,47 It is suggested that infants of mothers who had smoked in pregnancy often exhibit high rapid postnatal weight gain. 48,49 Smoking in pregnancy may also be a proxy for other social and lifestyle characteristics including poor dietary choices and socioeconomic status. 50 It is important to investigate whether addressing these potentially modifiable risk factors such as maternal smoking in pregnancy and high infant birth weight can reduce the risk of obesity in children and reduce the burden of intervention in the postnatal period.…”
Section: Figurementioning
confidence: 99%
“…However, none of these studies have examined how these feeding styles influence a child's body weight status. In addition, studies have not evaluated how pregnancy and infancy factors such as, overweight or obesity at the time of pregnancy (Catalano et al, 2009;Whitaker, 2004), smoking before, during, or after pregnancy Moschonis, Grammatikaki, & Manios, 2008;Olson, Strawderman, & Dennison, 2009), or a lack of breastfeeding during infancy (Karaolis-Danckert et al, 2008;Toschke et al, 2002) moderate the relationship between maternal beliefs and behavior and the child's body weight status. These issues represent significant gaps in the literature.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…One infancy factor is choosing not to breast feed, as breastfeeding during infancy has been shown to be protective against early childhood obesity ( Karaolis-Danckert et al, 2008;Toschke et al, 2002). Lastly, maternal smoking before, during, or after pregnancy has also been shown to be a risk factor for early childhood obesity Moschonis et al, 2008;Olson et al, 2009).…”
Section: Pregnancy and Infancy Factors Influencing Childhood Obesitymentioning
confidence: 99%